An Exploratory Study to Assess the Knowledge and Attitude Regarding Universal Precautions about Hepatitis B among Staff Nurses in Selected Hospitals, Punjab - Kaur, Kiranjit (International Journal of Nursing Research, 2023)
Background: The knowledge of nursing staff regarding hepatitis B virus (HBV) when their daily activities will be closely related to patients’ body fluids plays a vital role in minimizing the risk of acquiring HBV infection. Objective: We aimed to assess the knowledge regarding HBV infection among nursing staff. Materials and Methods: A descriptive cross-sectional study was conducted using a structured self-administered questionnaire among the nursing staff in Tagore Hospital, Jalandhar. Descriptive statistics was used to analyze the data. Results: Most (51%) of staff nurses had good knowledge followed by 44% who had excellent knowledge and few (5%) staff nurses with average knowledge score regarding universal precautions about hepatitis B. No staff nurse had poor knowledge score. All of the (100%) staff nurses had desirable attitude regarding universal precautions about hepatitis B. Conclusion: The staff had good knowledge regarding HBV infection and its preventive aspect.